Sustainable Fashion Retailing: A Research on Consumer Perceptions - Kose, Sirin Gizem; Aydin, Kenan (ISTANBUL UNIV, SCH BUSINESS, 2020)
The intense competition among fashion retailers makes constant product renewal and keeping the minimum price level obligatory. However, the fact that fast fashion orientation is criticized because of using toxic chemicals, causing water pollution and textile waste increased the movement toward sustainability activities in the fashion industry. This study investigated consumers' opinions on sustainable fashion with qualitative research. Consumers' perceptions and knowledge on sustainability and sustainability in fashion were researched, how consumers shape their clothing purchases and disposal behaviors were examined, and consumers' evaluations about fashion retailers that conduct sustainability activities and consumers' purchase intention for these fashion retailers were questioned. The data was gathered from 31 participants through in-depth interviews and themes were obtained, and models were about consumers' perception of sustainable fashion, the effect of sustainable fashion activities on retailers' image, and the sustainability effect on clothing purchasing and disposal. Research results show that consumers are aware of the adverse effects of the fashion industry, and they are conscious of their responsibility together with retailers. Furthermore, there is a lack of information regarding the content of sustainability activities and companies carrying out these activities. Consumers have favorable opinions on sustainable fashion retailing, and they think that sustainability activities support the fashion retailers' image. In order to convert the positive opinions into purchase behavior, communication activities, not compromising quality, design, and having a fair price are important.
Keywords: Sustainable fashion retailing; Qualitative research; Fashion retailing; Sustainability; Consumer perceptions; ORGANIC COTTON; PURCHASE; COMMUNICATION; CONSUMPTION; KNOWLEDGE; ATTITUDES; PRODUCTS; BEHAVIOR; TEXTILE; FUTURE; Business & Economics